PERANAN BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH DALAM PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN KABUPATEN MUARO JAMBI - Suaiba, Suaiba (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
This study aims to determine and analyze the Roles of Regional Tax and Retribution Board of Muaro Jambi and the constraints of the Regional Tax and Retribution Board of Muaro Jambi Regency in conducting the collection process. The type of research used is descriptive qualitative research with the nature of field research (Empirical). Information gathering techniques were conducted with in-depth interviews, field observations and literature. The results showed that the Regional Tax and Retribution Board of Muaro Jambi Regency could not reach the target of Land and Building Tax due to the many obstacles, both in the process of Planning, Organizing, Moving and in the Supervision process. The constraint is caused by the Regional Tax and Retribution Management Agency is the result of changes from the Regional Revenue Service to the Regional Tax and Retribution Board so that the human resources capability in accordance with BPPRD is also very much needed. The obstacle in the case of Collection of Land Tax and Rural and Urban Buildings is still the low level of supervision by the Regional Tax and Levy Management Agency from planning to the movement. Supervision is the key to the success of an organization, if supervision is weak then in every process will be found many obstacles. Regional Tax and Retribution Agency of Muaro Jambi Regency has made efforts in collecting Land and Rural Land and Urban Taxes. One of the efforts to face the constraints in tax collection is to socialize to the community about the usefulness and importance to pay the taxes, especially the Land and Rural Land and Urban Tax.